IMPROVEMENT OF MECHANISMS OF CREATIVE SELF-DEVELOPMENT OF FUTURE TEACHERS - Aripov Zoirjon Toirjonovich (Web of Journals Publishing, 2025)
This article is devoted to improvement of mechanisms of creative self-development of future teachers in the system of higher pedagogical education. The main mechanisms of professional and creative self-development of future teachers are considered.
Keywords: professional self-development, creative self-development, teaching technologies, future teachers, methods and ways.